Pengaruh Technopreneur Terhadap Pengembangan Usaha Kecil dan Menengah (UKM) - Effendy, Geraldo Revanska; Veri, Jhon (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Technopreneurship is a combination of technology and entrepreneurship that has significant potential in supporting the development of Small and Medium Enterprises (SMEs) in the digital era. This study aims to evaluate the impact of technopreneurship on the growth of SMEs in Indonesia, utilizing a Systematic Literature Review (SLR) method on 361 relevant articles from various academic databases, such as Google Scholar and Sinta. Data were analyzed using tools like Publish or Perish, Covidence, and VOSviewer to identify trends and relationships within the relevant literature. The findings indicate that technopreneurship plays a key role in enhancing SMEs' competitiveness through the adoption of digital technology, which supports operational efficiency, market expansion, and product innovation. However, several challenges, such as limited access to innovative financing, a shortage of skilled labor in technology, and insufficient digital infrastructure, remain major obstacles. Strategies such as continuous training, partnerships with the government and private sectors, and the use of e-commerce-based technology have proven effective in overcoming these challenges. This study provides crucial recommendations for stakeholders to strengthen technopreneurship as a primary driver of SME growth, particularly in facing the rapidly evolving digital transformation era